Clinical Characteristics of Pediatric Respiratory Tract Infection and Respiratory Pathogen Isolation During the Coronavirus Disease 2019 Pandemic - Tang, Xifeng; Dai, Ge; Jiang, Xiaohui; Wang, Ting; Sun, Huiming; Chen, Zhengrong; Huang, Li; Wang, Meijuan; Zhu, Canhong; Yan, Yongdong; Jiang, Wujun (Frontiers in Pediatrics, 2022)
Objective: To compare the clinical characteristics of pediatric respiratory tract infection and respiratory pathogen isolation during the coronavirus disease (COVID-19) epidemic to those recorded in 2018 and 2019. Methods: We included all children ranging from 28 days to 15 years old with respiratory tract infection who were admitted to the Department of Respiration, Children’s Hospital of Soochow University, between January 2018 and December 2020. Results: Compared to 2018 and 2019, the pathogen detection rate was significantly lower in 2020. With regard to single pathogen infection, in 2020, the detection rates of MP were the lowest in 3 years, while those of HRV were the highest. The positive rates of respiratory syncytial virus (RSV) and hMPV were less than those recorded in 2018 but similar to those in 2019. The rates of adenovirus (ADV) were lower than those recorded in 2019 but similar to those in 2018. There was no statistical difference in the positive rate of HBoV and PIV III over the 3 years. Infections in infants were significantly lower in 2020, while no significant difference was found among children aged 1 to 3 years. The detection rate of pathogens in children over 5 years old in 2020 was significantly lower than that recorded in the previous 2 years. The pathogen detection rates in the first and second quarters of 2020 were similar to those in the previous 2 years; however, the rates were reduced in the third and fourth quarters. As for coinfection, the positive rate was the lowest in 2020. In the previous 2 years, bacterial-viral was the most common type of mixed infection, among which mycoplasma infections were the most common. In 2020, viral-viral infections were the most common combination. Conclusion: The pathogen detection rate was significantly reduced in Suzhou City during the COVID-19 epidemic. Public interventions may prevent respiratory pathogen infections in children.